"I didn't know if I even really existed. But I do": music, dance, and the performance of male identity in Joker. Issue 1 (2nd January 2021) - Howell, Amanda
ABSTRACT: Like the Martin Scorsese films to which it is indebted – The King of Comedy (1982), Taxi Driver (1976) and Raging Bull (1980) – Joker (Phillips 2019) dramatises male identity as crisis-ridden and a matter of performance and emulation. Arguing for Joker as being concerned not just with masculinity but also whiteness, this discussion focuses on the role of music, dance, and ideologies of entertainment in the performative self-creation of Arthur Fleck (Joaquin Phoenix), who seeks, in the manner of Rupert Pupkin, Travis Bickle, and Jake La Motta, a coherent identity lent the affirmation of an audience.